Investigating the Challenges Facing the Teaching and Learning of Science and Technology in Selected Schools in the Ashanti Region of Ghana - Assem Humphrey-Darkeh; Kofi Owusu-Sekyere; Samuel Agyei Mensah (Journal of Science Learning, 2022)
The heightening public apprehension about instructional deliveries and the learning of science in Ghanaian schools have taken a different dimension as many shareholders keep interrogating the Government's pledge to ensure equity and quality science education for primary schools in the country. The study explored and defined the standing and quality of teaching, learning, and assessment of science and technology while finding the challenges faced by science educators at the JHS level in selected schools in the Ashanti region. The study randomly sampled science teachers' views and students in 27 schools from the 27 districts in the Ashanti Region in Ghana. Fourteen (14) and thirteen (13) schools were sampled from rural and urban areas. It was found that Government inadequately funds most schools. As a result, few qualified science teachers can handle the integrated science topics, among many other setbacks. It was concluded that the lack of infrastructure, TLMs, and other factors make the teaching and learning of science practically impossible. These challenges can be mitigated when specific, well-defined measures such as the provision of required infrastructure, teaching, learning materials (TLMs), and a few more are urgently implemented.